A Review of Ga₂O₃ Heterojunctions for Deep‐UV Photodetection: Current Progress, Methodologies, and Challenges - Alfred Moore; Saqib Rafique; Ciaran Llewelyn; Dan Lamb; Lijie Li (Advanced Electronic Materials)
Abstract In recent years, gallium oxide (Ga2O3) has drawn considerable research interest as an ultrawide‐bandgap semiconductor due to its promising applications in the power electronics, photodetection, and gas sensing. Moreover, Ga2O3 heterojunctions have emerged as a promising approach to address key limitations of Ga2O3 as a standalone material—most notably, its lack of p‐type doping capability. One of the key application areas for Ga2O3 and its heterojunctions is ultraviolet (UV) photodetection, which has gained significant attention yet remains a relatively nascent field with vast potential for further exploration and optimization. This review provides a detailed overview of the current state‐of‐the‐art in Ga2O3 technology, highlighting recent research advancements, key challenges, and emerging strategies aimed at overcoming these challenges. Specifically, it examines Ga2O3 heterojunctions for deep‐UV photodetection, analysing compatible electrode materials and assessing various substrates suitable for Ga2O3 growth to enhance device performance. This comprehensive review is designed to serve as an essential resource for researchers and engineers working with Ga2O3‐based heterojunctions, especially for applications in UV photodetection. Written with the needs of new entrants in mind, it aims to build a robust foundational understanding of Ga2O3 technology, supporting ongoing innovation and application expansion in this field.